Modulation of Intracellular ROS and Senescence-Associated Phenotypes of Xenopus Oocytes and Eggs by Selective Antioxidants - Alexander A. Tokmakov; Ken-Ichi Sato (Antioxidants, 2021)
Aging of oocytes and eggs diminishes their reproductive and developmental potential. It has been demonstrated previously that reactive oxygen species (ROS) contribute to accelerated aging of various cells. In the present study, we measured intracellular levels of ROS and investigated effects of several selective antioxidants (AOXs) on the viability and functional activity of aging oocytes and eggs of the African clawed frog Xenopus laevis. The fluorescent cell-permeable dye DCFDA, which is widely employed for ROS detection in cultured mammalian cells, was used to monitor ROS levels in the fresh and bench-aged oocytes and eggs by an optimized protocol. It was found that intracellular ROS contents were increased in frog oocytes and eggs aged for 48 h. It was further demonstrated using selective cell-permeable AOXs targeting different ROS-generating mechanisms, that the major source of ROS in Xenopus oocytes and eggs is the plasma membrane NADPH oxidase, and that mitochondrial generation contributes to the intracellular ROS content to a lesser extent. Targeted inhibition of NADPH oxidase with a natural organic compound apocynin reduced ROS levels significantly in Xenopus oocytes and eggs, maintained their normal phenotype and supported their functional competence. To our knowledge this is the first report concerning beneficial effects of apocynin on the isolated gamete cells, such as oocytes and eggs.